Edukasi Perilaku Investasi dan Penguatan Keputusan Finansial Investor Ritel di Kecamatan Praya Lombok Barat - Adrianda Anwar; I Gusti Agung Arista Pradnyani; Nila Rahayu; Yeldy Dwi Genadi (Universitas Mataram, 2026)
This community service activity aimed to strengthen public understanding of investment behavior and improve financial decision-making among retail investors in Praya, Central Lombok Regency. The main challenges faced by the community included low levels of financial literacy, limited understanding of investment risks, and the strong influence of psychological factors in investment decision-making processes. The program was implemented through several methods, including socialization, educational sessions, interactive discussions, and simple simulations related to investment behavior, risk management, and rational investment decision-making. The target participants consisted of the general public, university students, and beginner investors who had started to show interest in digital investment and capital markets. The results of the activity indicated that participants experienced improved understanding regarding the importance of financial literacy, the relationship between risk and return, and the ability to recognize investment behaviors influenced by emotional factors such as herd behavior and fear of missing out. In addition, participants also became more aware of the importance of selecting investment instruments that align with their risk profiles and personal financial goals. This community service activity contributed positively to increasing public awareness of the importance of conducting smart, rational, and responsible investment practices in response to the rapid growth of digital investment. Therefore, investment education programs can serve as a strategic effort to improve the quality of public financial decision-making in a sustainable manner.